Histological assessment for the effect of Cypermethrin in the skin of local breed rabbits - Bader Khatlan Hameed; Ali Khudheyer Obayes; Ayad Hameed Ebraheem (Tikrit Journal of Pure Science, 2020)
Research has been designed to focusing and evaluation the effect of cypermethrin as insecticide material in the skin of the rabbits. Cypermethrin was applied on the skin after shaving the dorso-lateral aspect of rabbits .The animals (12) were classified into four groups (A, B, C and D), three animals per group. Groups (B, C and D) were exposed to cypermethrin at doses (0.001, 0.005, 0.010)mg/kg respectively,  while  (A) was a control group. After ten days of drug's application, animals of group (D) were died at ending of the study because they received heavy dose. The groups (B and C) shown excitation  signs, followed by inhibition and depression of their activity. The animals of groups (A, B and C) were scarified and a specimens (0.5) cm3 of skin from the dorso- lateral aspect were obtained, washed with water and put in formalin (10)% then processed after (24) hours by using  histological technique, sectioned at (5)µm thickness, stained with Hematoxylin and Eosin a then examined under light microscopic at different powers.